Harmful Consequences of Air Pollution on Human Health in Nepal: A Review - Ghimire, Mayanath; Mishra, Anjay Kumar (International Research Journal of Parroha, 2025)
This paper examine and study the negative effects of air pollution on people's health in Nepal. Air pollution happens because of using bad fuel and not very good ways to produce energy. Usually, when the economy gets better, we need to use more energy. This directly affects people because it impacts the air we breathe. A detailed look at past records, along with a thorough examination, would be the approaches taken during the scientific evaluation. The Air Quality Index (AQI) shows different levels of air quality, with 0 to 50 being good, 51 to 100 being moderate, 101 to 200 being unhealthy, 201 to 300 being very unhealthy, and 301 to 500 being dangerous. In the Kathmandu valley of Nepal, local air pollutants like carbon monoxide, tiny particles in the air, and hydrocarbons make the air worse and can harm people's health. Families who have lower incomes and live in rural areas are not interested in having a better indoor air quality. The biggest reasons for air pollution come from energy, industry, and transportation. This is mainly due to using poor quality fuel and not using energy in good ways. Generally, when the economy grows, it needs more energy. Pollutants found in our area, like carbon monoxide, tiny particles, and hydrocarbons, can lower air quality and harm people's health. To handle and keep track of air pollution well, we need strong plans and rules.